Letter from Fritz Haber to Georg Bredig, December 1920 - Haber, Fritz (1920)
Letter from Fritz Haber (1868-1934) to Georg Bredig (1868-1944). Haber reminisces about studying in Leipzig with Bredig and the lasting impression their professors and mentors made.
Keywords: Haber, Fritz, 1868-1934; Bredig, Georg, 1868-1944; Ostwald, Wilhelm, 1853-1932; Hoff, J. H. van 't (Jacobus Henricus), 1852-1911; Chemists; Nobel Prize winners; Germany--Leipzig